Acid-catalyzed ethanol pretreatment of sugarcane bagasse enables electrochemically improved hard carbon anodes for sodium-ion batteries - Nethmi Kulanika Dayarathne; Eric Campbell; Mu Xiao; Jiaye Ye; Cheng Yan; Hongxia Wang; Dawei Wang; Yu Lin Zhong; Zhanying Zhang (Chemical Engineering Journal, 2026)

Benzalkonium chloride adaptation induces filamentation in Listeria monocytogenes HL06 and enhances its growth in pasteurized milk and pork sausage at 4 °C - Tao Yu; Xiaojie Jiang; Xiaobo Xu; Hongxia Zhu; David P. Hamilton; Shuxing Qiu; Junlei Yin; Xiaobing Jiang (Food Microbiology, 2026)

A domain embedding strategy for acoustic wave scattering by moving obstacles - Xuelong Gu; Hongxia Guo; Wenkai Yu; Guanghui Hu; Qi Wang (Computer Physics Communications, 2026)

Adaptability of Chaetomorpha valida (Ulvophyceae) spores to salinity, nutrients and water flow in aquaculture ponds and its invasive evaluation - Dongyue Li; Ronglian Xing; Rui Li; Xuebin Cao; Shujun Hu; Xiaojing Pan; Hongxia Zhang; Lihong Chen; Zhen Yu (Aquatic Ecology, 2026)

Altered amplitude of low-frequency fluctuations in herpes simplex encephalitis: a resting-state fMRI study and associations with anxiety - Hongxia Bai; Qi Zhou; Hui Li; Cailing Zhao; Ying Bai; Yangli Yu; Jueyue Yan; Lingli Lou (Brain Imaging and Behavior, 2026)

Retraction notice to "Asiatic acid reverses cisplatin resistance in A549/DDP cells by activating the P38 MAPK/slug pathway" [Tissue Cell 98 (2026) 103145] - Min Yu; Qian Zhang; Wenli Shang; Shenghong Wei; Hongxia Wen; Shufen Huo; Xiang Li; Xuan Li; Heng Zhang; Yingxuan Tian (Tissue and Cell, 2026)

Enhancing large-scale streamflow prediction by coupling structural inductive bias with meta-learning - Xuan Tang; Yuting Zhao; Yuan Yu; MingRui Yu; Guanghua Qin; Hongxia Li (Journal of Hydrology, 2026)

Experimental and computational investigation on CO2 absorption kinetics of five piperazine-derived cyclic amines in aqueous/ether-water systems - Min Zhou; Ningbo Yu; Dongyang Li; Minghao Wang; Hongxia Gao; Zhiwu Liang (Journal of Cleaner Production, 2026)

Distribution and influencing factors of soil and groundwater pollution at pharmaceutical sites in China - Ying Hou; Yi Shi; Weiguang Zhao; Yifei Liu; Nuchao Xu; Hongxia Hu; Haoyuan Wang; Meng Yu; Bochao Zhang; Guizhen Hao; Hongguang Zheng; Juejun Yao; et al. (Journal of Environmental Sciences, 2026)

Development of a hydrazinolysis method for the determination of vinclozolin in foods by SPE and GC–MS/MS - Hongxia Tang; Yubo Li; Qinyi Sheng; Rui Yu; Dongwei Wang; Lin Ma; Guangyue Wen; Maofeng Dong; Xianbin Li; Li Zhao (Food Chemistry, 2026)

Unveiling the solvent composition dependence of amine kinetics in DMSO-water systems: Stopped-flow intrinsic rate analysis with DFT/MD mechanistic validation - Min Zhou; Guanjun Chen; Ningbo Yu; Zhiwu Liang; Hongxia Gao (Chemical Engineering Journal, 2026)

Cisplatin-induced renal injury: ROS-mediated oxidative stress — mechanism and antioxidant intervention strategies - Zhiwei Huang; Linpeng Yang; Yupeng Chu; Hang Yu; Xiaoyan Fu; Meifang Liu; Xianhong Du; Liyuan Wang; Hongxia Zhang (Chemico-Biological Interactions, 2026)

Spherical silica-alumina with mixed acid structure for effective catalysis of the ketalization of glycerol with acetone - Hongxia Wang; Yiwang Tang; Yuqing Cheng; Xintong Liu; Gang Yu; Xiulan Xin (Biomass and Bioenergy, 2026)

Overexpression of PagAPX8 promotes poplar growth and enhances tolerance to drought and salt stress - Yuanyuan Shang; Zhaoyang Tian; Yingxin Zhang; Shuo Song; Yu Guo; Zibin Song; Hongling Mo; Kunlin Wang; Yanqiu Zhao; Hongxia Zhang; Lizi Zhao (Plant Cell Reports, 2026)

High-sensitivity Temperature Sensing via Color Change: A Study on the Thermal Coupling and Non-thermal Coupling Energy Levels in YVO4:Tm3+/Er3+ - Zhensheng Lu; Hongxia Tang; Meilin Song; Changxing Yu; Changwen Wang (Journal of Fluorescence, 2026)

Hexavalent chromium inhibits testosterone synthesis in bovine testicular leydig cells through mitochondrial damage via BNIP3 - Hongxia Li; Jia Liu; Liwei Huang; Yu Cheng; Guoqing Zhao; Xiaolong Pan; Lijuan Huang; Pengkang Song; Le Zhao; Xuanqi Yu; Juan Xiong; Qing Tian; et al. (Reproductive Biology, 2026)

The autophagy-related protein OsCOST1 negatively regulates the salt tolerance in rice - Xiaole Fan; Zimeng Pan; Xiaotong Xu; An Yan; Bei Li; Ying Zhao; Xiaotong Guo; Chunyan Yu; Hongxia Zhang (Plant Cell Reports, 2026)

Petrogenesis of the volcanic glass from the Central Lau Basin: Insight into the nature of underlying upper mantle - Xiongyue Li; Xijun Liu; Zhenglin Li; Liyan Tian; Paterno R. Castillo; Hongxia Yu; Yuzhen Liu; Xiangsong Wang (Journal of Asian Earth Sciences, 2026)

Construction of SnO2/Bi2O2CO3 Z-type heterojunction for photocatalytic degradation of humic acid under sunlight - Muxi Zhang; Chenchen Liao; Bin Dong; Wenjie Lin; Yu Chen; Penghui Yao; Xiaojie Sun; Hongxia Zhang (Environmental Research, 2026)

Technological evolution and industrial scaling of Spirulina in China: a four-decade review - Kexin Xu; Ronglian Xing; Kang Wang; Song Qin; Zhili Yu; Hongxia Zhang; Rui Li; Zhen Yu; Lihong Chen (Journal of Applied Phycology, 2026)

Promoting Aquatic Animal Health and Water Quality: A Systematic Review on Probiotics, Prebiotics and Synbiotics in Aquaculture - Yaxin Wen; Miao Wang; Haoran Wang; Shilin Liu; Ronglian Xing; Hongxia Zhang; Lihong Chen; Rui Li; Zhen Yu (Fishes, 2026)
Background: Aquaculture, a vital component of global food security, faces sustainability challenges due to intensive farming practices, including water pollution, disease outbreaks, and antibiotic overuse. Probiotics, prebiotics, and synbiotics have emerged as eco-friendly alternatives to antibiotics. However, research results remain heterogeneous across aquatic species and intervention strategies. Methods: Following PRISMA 2020, we searched two databases (up to January 2026) for in vivo trials. Two reviewers screened and extracted data, and 177 eligible studies were ultimately included, covering single-/multi-strain probiotics (SSP/MSP), live/inactivated microbial preparations, and diverse synbiotic formulations. Results: Among 177 studies, Bacillus spp. were the most widely reported and effective probiotic strains. MSP and synbiotics exhibited superior efficacy in boosting aquatic animal growth performance and disease resistance over SSP in 68% of the included trials. Probiotics act through the competitive exclusion of pathogens, immune modulation, and enhanced digestive enzyme activity; prebiotics selectively stimulate beneficial gut microbiota, improving nutrient absorption and immune function through metabolites such as short-chain fatty acids; synbiotics combine the advantages of both, exerting synergistic effects. Furthermore, as water additives or fermented feed ingredients, probiotics reduce nitrogenous waste and organic pollutants, contributing to bioremediation. Conclusions: All three additives are effective. Standardized application protocols and long-term trials are needed for sustainable aquaculture. This review provides a unified evidence-based foundation for the rational use of these additives in aquaculture.

Pharmaceutical-dominated organic contaminants in plateau lakes: Suspect and non-target screening, PBT risk, and structure-based risk markers - Liben Chou; Wanshu Zhu; Rong Zhang; Jinsha Jin; Kai Huang; Lu Dong; Mengke Jin; Wenrui Luo; Yan Mao; Xiangyi Yu; Haoyue Tan; Jing Guo; et al. (Water Research, 2026)

The cytochrome P450 protein AtCYP85A2 increases stresses tolerance through promoting brassinosteroid biosynthesis in transgenic tomato - Yuanyuan Shang; Zhaoyang Tian; Kaifeng Lu; Yu Guo; Shuo Song; Zibin Song; Hongling Mo; Lizi Zhao; Hongxia Zhang; Yanqiu Zhao (Plant Science, 2026)

Dual-Regulated Ru by alloying and Metal-Substrate interaction for Energy-Efficient hydrazine Oxidation-Paired hydrogen production - Qijing Zhang; Hongxia Yu; Siyi Wang; Haibo Li; Suyuan Zeng; Rui Li; Qingxia Yao; Qi Zhang; Ruru Chen; Lijian Meng; Konggang Qu (Fuel, 2026)

Preparation of the core-shell grained Li4SiO4 pebble with an excellent CO2 adsorption capacity by solidification of suspension - Shuxian Wu; Jingli Shi; Hailiang Wang; Peng Yang; Aixia Guo; Penghe Xu; Chaoyang Jia; Lina Zheng; Feng Yu; Hongxia Lu; Hongliang Xu; Hailong Wang (Chemical Engineering Journal, 2026)

Quantitative prediction of zebrafish reproductive impairment via androgen receptor-driven adverse outcome pathway - Xuan Liu; Hongxia Yu; You Song; Wei Shi; Hongling Liu (Aquatic Toxicology, 2026)

Regulation of ovarian maturation in Macrobrachium nipponense by the ribonucleotide reductase M1 subunit - Hongxia Jiang; Zhenzhuo Wang; Wenshan Cui; Xiao Li; Yongjing Li; Meng Zhang; Lei Wang; Miao Yu; Zhigang Qiao (Marine Life Science & Technology, 2026)

RETRACTED: Asiatic acid reverses cisplatin resistance in A549/DDP cells by activating the P38 MAPK/Slug pathway - Min Yu; Qian Zhang; Wenli Shang; Shenghong Wei; Hongxia Wen; Shufen Huo; Xiang Li; Xuan Li; Heng Zhang; Yingxuan Tian (Tissue and Cell, 2026)

A global meta-analysis of N2O emission-yield trade-offs in wheat, rice and maize systems under different agricultural management - Jia Zeng; Yu Li; Xing Wang; Qi Zhang; Ying Lu; Jingjing Wang; Yang Guo; Hongxia Wang; Gang Yang; Chengjie Ren; Gaihe Yang; Xinhui Han (Resources, Conservation and Recycling, 2026)

Pocket-based lead optimization strategy for the design of laccase inhibitors as potential antifungal agents - Xiaoming Zhang; Xuebo Zhang; Xingxing Lu; Tengda Sun; Zhengxin Zhou; Huan Xu; Xinling Yang; Hongxia Duan; Xili Liu; ShuJing Yu; Li Zhang; Yun Ling (Pesticide Biochemistry and Physiology, 2026)

Rational design of structurally rigidified ketone-peptide deformylase inhibitors with enhanced membrane permeability for combating gram-negative bacterial infections - Zhonghui Zhang; Jidi Hu; Maoqing Shi; Xiaoxiao Gong; Taoda Shi; Hongxia Li; Yu Qian; Wenhao Hu (Molecular Diversity, 2026)

DNAJB6 as an immuno-oncogenic hub in liver hepatocellular carcinoma: multi-omic profiling reveals prognostic significance and therapeutic vulnerability - Yiting Deng; Jin Li; Peng Wang; Xuelian Luo; Hongxia Xu; Yu Xiao; Zhenchuan Wang; Yifei Lu; Ying Chen; Feng Ge (Journal of Molecular Histology, 2026)

Prostaglandin E2 synthetase (PGES) gene from Procambarus clarkii: cDNA cloning and functional analysis in ovarian development - Xiao Li; Shuaishuai Zhang; Xuewei Liu; Wenshan Cui; Zhenzhuo Wang; Meng Zhang; Lei Wang; Miao Yu; Yongjing Li; Zhigang Qiao; Hongxia Jiang (Aquaculture, 2026)

Reutilization of Fenton sludge as an iron source for the promotion of anammox processes: Performance and microbial community - Zhinan Wu; Weijie Mao; Xikun Zhou; Qi Zhang; Xueqing Shen; Yiyang Liu; Hongxia Yu; Fei Chen (Process Safety and Environmental Protection, 2026)

Study on dual-path inhibition mechanisms and multiscale structure-activity relationships in CO2 absorption kinetics of 3AP-based water-lean alcohol solutions - Ningbo Yu; Qiang Sun; Minghao Wang; Huiying Liao; Zhiwu Liang; Hongxia Gao (Chemical Engineering Journal, 2026)

Mapping the Evolution of Experimental Autoimmune Encephalomyelitis Research (2000–2024): A Global Bibliometric and Knowledge Domain Analysis - Zhihua Dong; Yu He; Taisong Yin; Kun Xu; Xueli Liu; Hongxia Han; Lijuan Song; Zhibin Ding; Xinyi Li; Yanbing Su (Molecular Neurobiology, 2026)

Panax Quinquefolium L. polysaccharide-protein conjugated nanoparticle stabilized pickering emulsion: Structural characteristics, in vitro digestive stability, and its antioxidant protective effect in HepG2 cells - Xiaohui Yan; Zhenhua Feng; Xiao Wang; Hongxia Yu; Feng Liu; Wei Liu (Food and Bioproducts Processing, 2025)

Dual-responsive carboxymethyl cellulose-based hydrogel sensor with antibacterial activity for wound monitoring and infected wound repair - Zhengjie Yu; Fanwei Zeng; Yuejin Cai; Zijie Wang; Ze Chen; Ruizi Wang; Qingfeng Sun; Xiaodong Tang; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

MAZ-mediated LAMA5 transcription activation promotes gastric cancer progression through the STAT3 signaling - Yu Wang; Jiazhong Xu; Hongxia Zhang; Xiaobo Guo; Hongjun Liu; Qinhui Sun (Functional & Integrative Genomics, 2025)

The high-affinity K+ transporter IbHAK5 enhances potassium ion absorption and improves root morphology in sweetpotato (Ipomoea batatas) - Rong Jin; Peng Zhao; Mengxiao Yan; Ming Liu; Weijuan Fan; Qiangqiang Zhang; Xiaoya Zhu; Jing Wang; Yongchao Yu; Jun Yang; Hongxia Wang; Zhonghou Tang (Transgenic Research, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Transcriptome to reveal the immunological defenses in mandarin fish (Siniperca chuatsi) skin with LPS and poly (I:C) infection - Yawei Shen; Jiong Gao; Meng Zhang; Yongjing Li; Rahma Sakina Said Aly; Lei Wang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Xiaowu Chen (Fish & Shellfish Immunology, 2025)

Overexpression of PtrCWINV2 accelerates shoot growth and wood development in hybrid poplar (Populus davidiana × Populus bolleana) - Ruichao Liu; Hongying Wang; Junjie Zhang; Jiangting Yang; Pan Guo; Yueting Qi; Xiaotong Guo; Chaoxia Lu; Chunyan Yu; Hongxia Zhang (Plant Cell Reports, 2025)

Genesis of the Debao Sn-Cu Deposit in South China: Insights from Pb-S-He-Ar Isotopes - Jian Zhang; Lichuan Zhang; Quan Ou; Pan Qu; Yinqiao Zou; Hongxia Yu (Journal of Earth Science, 2025)

Late Jurassic to Early Cretaceous mafic to felsic magmatism reveals the coupled processes of crustal growth and thinning in Southeast China - Yulin Wang; Jinbao Yang; Xijun Liu; Hongxia Yu; Zhenglin Li; Tengpeng Li; Zhenzhen Xu; Yiting Yuan (Geochemistry, 2025)

Smart eutectogel with antibacterial activity for efficiently treating multidrug resistant infection, real-time monitoring and diabetic wound repair - Zijie Wang; Baiwen Qi; Ruizi Wang; Ze Chen; Jingming Zhong; Zheng Wang; Qingfeng Sun; Aixi Yu; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

Algicidal activity and mechanism of novel Bacillamide a derivative against red tide algae Skeletonema costatum and Prorocentrum minimum - Huili Li; Xiaoxue Li; Yi Liu; Ronglian Xing; Hongxia Zhang; Wenguang Jia; Lihong Chen; Rui Li; Zhen Yu; Zhihong Tang (Pesticide Biochemistry and Physiology, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Genome-wide association study reveals growth-related mutations and candidate genes at early growth stages in largemouth bass (Micropterus salmoides) - Xiao Ma; Dongcai Chen; Zhilin Jia; Yue Xu; Zhigang Qiao; Lei Wang; Hongxia Jiang; Miao Yu; Yongjing Li; Xiaotian Gao; Chunlong Zhao; Yawei Shen; et al. (Aquaculture, 2025)

Multi-omics integrative analysis reveals the molecular mechanisms of muscle adaptive changes in largemouth bass (Micropterus salmoides) under water flow stress in recirculating aquaculture - Lei Wang; Chang Liu; Lingran Wang; Jiaxin Xu; Jiajun Zheng; Yuyue Xu; Zhan Jin; Di Feng; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao (Aquaculture, 2025)

Impact of funnel-shaped recirculating aquaculture system on the growth, health, and muscle quality of largemouth bass (Micropterus salmoides) - Jiaxin Xu; Chang Liu; Jiajun Zheng; Jianhua Wang; Lingran Wang; Di Feng; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Lei Wang (Aquaculture, 2025)

Sustained Tl(I) removal by α-MnO2: Dual role of tunnel structure incorporation and surface catalytic oxidation - Wanpeng Chen; Xiaoliu Huangfu; Yu Liu; Yuheng Huang; Xiaoling Zhang; Sisi Wu; Hongxia Liu; Qiang He (Journal of Hazardous Materials, 2025)

The insights into the phage communities of fermented foods in the age of viral metagenomics - Huadong Zhang; Hongxia Zhang; Hai Du; Xiaowei Yu; Yan Xu (Critical Reviews in Food Science and Nutrition, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Origin and evolution of the Qiangtang block, northern Tibetan Plateau: New insights from detrital zircon U-Pb geochronology and Lu-Hf isotopic compositions - Min Liu; Xijun Liu; Hao Wu; Yao Xiao; Zhenglin Li; Hongxia Yu (Journal of Asian Earth Sciences, 2025)

A new HCM heart sound classification method based on weighted bispectrum features - Fang Yu; Huang Zhiyuan; Leng Hongxia; Dongbo Liu; Wang Weibo (Physical and Engineering Sciences in Medicine, 2025)

Genome-wide association analysis study on host resistance against the Aeromonas veronii of largemouth bass Micropterus salmoides - Meng Zhang; Xiao Ma; Zerui Wang; Yuqing Han; Zhilin Jia; Dongcai Chen; Yue Xu; Zhigang Qiao; Xinyu Jiang; Lei Wang; Hongxia Jiang; Miao Yu; et al. (Fish & Shellfish Immunology, 2025)

Investigating residual trace metals in recombinant monoclonal antibodies to facilitate drug development with LC-UV-ICPMS-HRMS - Xueqing Zhao; Jikang Wu; Yu Zhang; Hongxia Wang; Haibo Qiu; Ning Li (Analytica Chimica Acta, 2025)

Effect of exercise intensity on growth performance, serum biochemistry parameters, liver antioxidant capacity, and intestinal health of common carp (Cyprinus carpio) in recirculating aquaculture system - Lingran Wang; Chang Liu; Di Feng; Jintai Huang; Zhan Jin; Fangran Ma; Jiaxin Xu; Yuyue Xu; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao; et al. (Aquaculture, 2025)

Physiological and immune responses of largemouth bass (Micropterus salmoides) under the regulation of exercise intensity: An integrated perspective of blood, liver and intestinal analysis - Chang Liu; Lingran Wang; Jiaxin Xu; Jiajun Zheng; Yuyue Xu; Zhan Jin; Di Feng; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Lei Wang (Aquaculture, 2025)

Transcription factor PdMYB118 in poplar regulates lignin deposition and xylem differentiation in addition to anthocyanin synthesis through suppressing the expression of PagKNAT2/6b gene - Shuo Song; Wei Guo; Yu Guo; Erkun Chao; Sujie Sun; Lizi Zhao; Yanqiu Zhao; Hongxia Zhang (Plant Science, 2025)

A novel Ag/Bi/Bi2O2CO3 photocatalyst effectively removes antibiotic-resistant bacteria and tetracycline from water under visible light irradiation - Suo Wang; Changyu Li; Huanshun Yin; Bin Gao; Zhengkun Yu; Yunlei Zhou; Jun Wang; Hongxia Xu; Jichun Wu; Yuanyuan Sun (Environmental Research, 2025)

Treatment of sludge hydrothermal carbonization wastewater by ferrous/sodium percarbonate system: Effect of wastewater composition and role of coagulation and oxidation - Liming Liu; Luna Zhao; Shiyun Jin; Wei Zou; Hongxia Wang; Yu Xie; Changlan Hou; Yunbo Zhai; Pingping Luo (Water Research, 2024)

Association between blood microplastic levels and severity of extracranial artery stenosis - Hongxiang Yu; Hongxia Li; Can Cui; Yingying Han; Yaping Xiao; Bei Zhang; Gang Li (Journal of Hazardous Materials, 2024)

Effects of varied exercise intensities on growth, muscle quality and volatile compounds in largemouth bass (Micropterus salmoides) cultured in recirculating aquaculture system - Chang Liu; Lingran Wang; Jiaxin Xu; Di Feng; Jiajun Zheng; Zhan Jin; Fangran Ma; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Lei Wang (Aquaculture, 2024)

Environmental concentrations of 6PPD and 6PPD-Q cause oxidative damage and alter metabolism in Eichhornia crassipes - Yichen Ge; Jinzheng Liu; Ruiying Shi; Xiang Li; Aurang Zeb; Qi Wang; Jianling Wang; Yuexing Zhao; Miao Yu; Chuan Yin; Hongxia Xiong; Weitao Liu (Science of The Total Environment, 2024)

Late Triassic basaltic andesites unveil inception of Neo-Tethys Ocean in Gyaca area of Tethyan Himalaya - Qinwen Gao; Feng Huang; Song Zhang; Yunchuan Zeng; Mingjian Li; Shuo Wang; Chenyuan Hua; Hongxia Yu; Yinhui Zhang; Jifeng Xu (Lithos, 2024)

Revealing the effects of functional group in organic linkers on properties of metal organic frameworks electrode and their performance in supercapacitors - Le Pang; Yaojie Lei; Yu Zou; Feng Yu; Fan Feng; Jiahui Lu; Wei Kong Pang; Zhe Liu; Porun Liu; Anthony P. O’Mullane; Guoxiu Wang; Hongxia Wang (Chemical Engineering Journal, 2024)

Multicolor emissive hyperbranched polysiloxanes from enhanced spatial electronic communication for security encryption and bacteria imaging - Lihua Bai; Hengyu Li; Jiyan Gao; Xiangtao Ma; Xiangrong Liu; Hongxia Yan; Shunsheng Zhao; Chunxia Yu; Juanmin Li (Chemical Engineering Journal, 2024)

Elucidating the underlying formation mechanism of spongy tissue in ‘Keitt’ mango via metabolomics and proteomics analysis - Xiaowei Ma; Bin Liu; Jianan Yao; Yuehua Zhang; Wentian Xu; Yabing Yang; Kunliang Xie; Dong Yu; Hongxia Wu; Songbiao Wang (Postharvest Biology and Technology, 2024)

Quorum sensing regulating the heterogeneous transformation of antibiotic resistance genes in microplastic biofilms - Xiaowei Liu; Chuang Huang; Hongxia Yu; Yaning Yang; Lulu Ma; Bin Zhao; Tianyang Zhong; Lilan Zhang; Weihua Peng; Wenwen Gong; Yan Ding (Journal of Environmental Chemical Engineering, 2024)

Modulating the stability and gastrointestinal tolerance of lycopene in low-oil gelatin emulsions by constructing cellulose network barrier - Xin Feng; Hankun Zhu; Hongjie Dai; Yong Yu; Hongxia Tan; Mi Tang; Kangting Sun; Yapeng Lu; Yugang Liu; Liang Ma; Yuhao Zhang (Food Hydrocolloids, 2024)

Evaluation of forage quality in various soybean varieties and high-yield cultivation techniques - Baiquan Sun; Shan Yuan; Mahmoud Naser; Yanfeng Zhou; Hongchang Jia; Yang Yu; Xiangyu Yao; Tingting Wu; Wenwen Song; Bingjun Jiang; Hongxia Dong; Chunlei Zhang; et al. (Field Crops Research, 2024)

The improvement of tyrosol bioavailability by encapsulation into liposomes using pH-driven method - Yexuan Yao; Li Ma; Chengwei Yu; Ce Cheng; Hongxia Gao; Teng Wei; Litong Li; Zhiyue Wang; Wei Liu; Zeyuan Deng; Liqiang Zou; Ting Luo (Food Chemistry, 2024)

4D printing of betanin/gelatin/nano-chitin complexes-functionalized surimi via disulfide bonds, and its applicability in dysphagia diets - Juncheng Zhu; Yuxin Yang; Shihao Qiao; Hongjie Dai; Hai Chen; Yu Fu; Liang Ma; Hongxia Wang; Yuhao Zhang (Food Hydrocolloids, 2024)

Cotransport of aged biochar colloids and thallium(I) in water-saturated porous media: Impact of the ionic strength, pH and aging degree - Shuangrui Yang; Yu Cao; Zhiheng Li; Chengxue Ma; Yuheng Huang; Die Hu; Hongxia Liu; Xiaoliu Huangfu (Science of The Total Environment, 2024)

Unlocking the potential of high-voltage aqueous rechargeable batteries: Achievements and perspectives - Feng Yu; Lide Li; Le Pang; Songjun Yang; He Liu; Cong Guo; Weizhai Bao; Jingfa Li; Guozhen Zhang; Faxing Wang; Hongxia Wang (Chemical Engineering Journal, 2024)

Bioinspired wet adhesive carboxymethyl cellulose-based hydrogel with rapid shape adaptability and antioxidant activity for diabetic wound repair - Hongxia Xie; Ge Shi; Ruizi Wang; Xueyu Jiang; Qianqian Chen; Aixi Yu; Ang Lu (Carbohydrate Polymers, 2024)

Enhanced photocatalytic ammonia oxidation over WO3@TiO2 heterostructures by constructing an interfacial electric field - Zhaonian Li; Daorong Li; Zhanzhao Feng; Shuqi Lv; Qingxuan Zhang; Yanru Yu; Ying Tian; Runfeng Huang; Hongxia Chen; Kunfeng Zhang; Hongxing Dai (Chemosphere, 2024)

Enhanced barrier and antioxidant properties of gelatin films by structural-colored bioactive materials for food packaging - Sitong Liu; Shihao Qiao; Juncheng Zhu; Yuxin Yang; Hai Chen; Hongjie Dai; Hankun Zhu; Yong Yu; Liang Ma; Yuhao Zhang; Hongxia Wang (Food Hydrocolloids, 2024)

Identify organic contaminants of high-concern based on non-targeted toxicity testing and non-targeted LC-HRMS analysis in tap water and source water along the Yangtze River - Shaoqing Zhang; Liben Chou; Wenxuan Zhu; Wenrui Luo; Chi Zhang; Jingfan Qiu; Meishuang Li; Haoyue Tan; Jing Guo; Chang Wang; Keng Tu; Kefan Xu; et al. (Water Research, 2024)

Exploring correlations between soy sauce components and the formation of thermal contaminants during low-salt solid-state fermentation - Feng Li; Yuting Wang; Hongxia Liao; You Long; Qiang Yu; Jianhua Xie; Yi Chen (Food Research International, 2024)

Designing gelatin microgels by moderate transglutaminase crosslinking: Improvement in interface properties - Hongjie Dai; Mengsi Xia; Xin Feng; Liang Ma; Hai Chen; Hankun Zhu; Yong Yu; Hongxia Wang; Yuhao Zhang (Food Hydrocolloids, 2024)

Transcriptomic analysis of hydrogen peroxide-induced liver dysfunction in Cyprinus carpio: Insights into protein synthesis and metabolism - Wenrong Feng; Yuanfeng Xu; Shengyan Su; Fan Yu; Jianlin Li; Rui Jia; Changyou Song; Hongxia Li; Pao Xu; Yongkai Tang (Science of The Total Environment, 2024)

Inhibitory effect and mechanism of algicidal bacteria on Chaetomorpha valida - Yaqi Geng; Ronglian Xing; Hongxia Zhang; Guoning Nan; Lihong Chen; Zhen Yu; Chuyao Liu; Huili Li (Science of The Total Environment, 2024)

Mechanism of interaction between ascorbic acid and soil iron-containing minerals for peroxydisulfate activation and organophosphorus flame retardant degradation - Xiaona Dong; Miaomiao Dai; Tongyi Yang; Lulu Chen; Hongxia Yu; Liwei Chen; Rudong Zhao; Canlan Jiang (Environmental Research, 2024)

Erratum to: CD146 as a promising therapeutic target for retinal and choroidal neovascularization diseases - Bai Xue; Ping Wang; Wenzhen Yu; Jing Feng; Jie Li; Rulian Zhao; Zhenglin Yan; Xiyun Yan; Hongxia Duan (Science China Life Sciences, 2024)

Melatonin decreases GSDME mediated mesothelial cell pyroptosis and prevents peritoneal fibrosis and ultrafiltration failure - Hongxia Ruan; Xuejuan Li; Lina Zhou; Zihan Zheng; Rulin Hua; Xu Wang; Yuan Wang; Yujie Fan; Shuwen Guo; Lihua Wang; Shafiq ur Rahman; Ziwei Wang; et al. (Science China Life Sciences, 2024)

Identification, characterisation and expression analysis of peanut sugar invertase genes reveal their vital roles in response to abiotic stress - Tingting Mao; Yaru Zhang; Wenwen Xue; Yu Jin; Hongfei Zhao; Yibo Wang; Shengnan Wang; Shengjie Zhuo; Feifei Gao; Yanping Su; Chunyan Yu; Xiaotong Guo; et al. (Plant Cell Reports, 2024)

CNN Multibeam Seabed Sediment Classification Combined with a Novel Feature Optimization Method - Michael Anokye; Xiaodong Cui; Fanlin Yang; Miao Fan; Yu Luo; Hongxia Liu (Mathematical Geosciences, 2024)

Unveiling the spatial patterns and potential sources of black carbon in lake sediments from diverse developing areas in a representative mining and metallurgy region of Central China - Zirong Xiao; Liping Yu; Jia Li; Wen Zhu; Yuxiao Li; Yanni Li; Changlin Zhan; Hongxia Liu; Jiaquan Zhang; Yanan Wang; Shan Liu (Journal of Soils and Sediments, 2024)

Mechanisms for thallium(I) adsorption by zinc sulfide minerals under aerobic and anaerobic conditions - Yu Liu; Wanpeng Chen; Yuheng Huang; Zhiheng Li; Changsheng Li; Hongxia Liu; Xiaoliu Huangfu (Journal of Hazardous Materials, 2024)

Insight into the long-term nonoxidative immobilization of thallium on birnessite - Wanpeng Chen; Yu Liu; Yuheng Huang; Die Hu; Hongxia Liu; Xiaoliu Huangfu (Journal of Cleaner Production, 2024)

Cotransport of Tl(I) and kaolinite colloids in water-saturated porous media: Two systems with different components - Zhiheng Li; Jinni Yao; Yu Cao; Chengxue Ma; Shuangrui Yang; Hongxia Liu; Li Gu; Wanpeng Chen; Xiaoliu Huangfu (Journal of Environmental Chemical Engineering, 2023)

Dietary supplementation with American ginseng dietary fiber ameliorates intestinal mucosal barrier injury in immunosuppressed mice - Jiyue Sha; Zhengbo Liu; Hongxia Yu; Xiaohui Huo; Jiajia Wang; Yuanyuan Duan; Wei Li; Di Qu; Zhiman Li; Jianbo Chen; Xueqing Li; Yinshi Sun (Food Bioscience, 2023)

Characterization and immune functional analysis of two new type I crustins in the oriental river prawn Macrobrachium nipponense - Hongxia Jiang; Shuaishuai Zhang; Xuewei Liu; Yizheng Li; Huanxin Li; Ran Zhang; Yuhua Li; Meng Zhang; Lei Wang; Miao Yu; Zhigang Qiao; Xuejun Li (Aquaculture, 2023)

Transcriptome analysis for key softening-related genes in 'Docteur Jules Guyot' pear (Pyrus communis L.) - Xiaonan Dai; Fudong Jiang; Qingyu Li; Xinhui Yu; Xiaofei Xu; Weilin Cao; Tingting Guo; Zhizhong Song; Aidi Zhang; Hongxia Zhang; Jianzhao Li (Postharvest Biology and Technology, 2023)

Effect of different types of nanocellulose on the structure and properties of gelatin films - Perpetual Ogechi Onyeaka; Hongjie Dai; Xin Feng; Hongxia Wang; Yu Fu; Yong Yu; Hankun Zhu; Hai Chen; Liang Ma; Yuhao Zhang (Food Hydrocolloids, 2023)

Stabilization of capsanthin in physically-connected hydrogels: Rheology property, self-recovering performance and syringe/screw-3D printing - Hongxia Wang; Chaoyang Wu; Juncheng Zhu; Yang Cheng; Yuxin Yang; Shihao Qiao; Bo Jiao; Liang Ma; Yu Fu; Hai Chen; Hongjie Dai; Yuhao Zhang (Carbohydrate Polymers, 2023)

Hypothermia-mediated oxidative stress induces immunosuppression, morphological impairment and cell fate disorder in the intestine of freshwater drum, Aplodinotus grunniens - Jianxiang Chen; Pao Xu; Haibo Wen; Miaomiao Xue; Qingyong Wang; Jiyan He; Changchang He; Shengyan Su; Jianlin Li; Fan Yu; Wenrong Feng; Meiyao Wang; et al. (Aquaculture, 2023)

The Toll pathway and Duox-ROS system are required for the clam antibacterial immune response in the hepatopancreas - Jiajia Yu; Shuangshuang Teng; Xin Yue; Hongxia Wang; Baozhong Liu (Aquaculture, 2023)

Deep mining of reported emerging contaminants in China's surface water in the past decade: Exposure, ecological effects and risk assessment - Jing Guo; Keng Tu; Liben Chou; Ying Zhang; Si Wei; Xiaowei Zhang; Hongxia Yu; Wei Shi (Water Research, 2023)

The occurrence, tissue distribution, and PBT potential of per- and polyfluoroalkyl substances in the freshwater organisms from the Yangtze river via nontarget analysis - Zhaoyu Jiao; Nanyang Yu; Jiadi Mao; Qian Yang; Liping Jiao; Xuebing Wang; Wei Shi; Hongxia Yu; Si Wei (Journal of Hazardous Materials, 2023)

The moisture adsorption, caking, and flowability of silkworm pupae peptide powders: The impacts of anticaking agents - Yu Fu; Fali Luo; Liang Ma; Hongjie Dai; Hongxia Wang; Hai Chen; Hankun Zhu; Yong Yu; Yong Hou; Yuhao Zhang (Food Chemistry, 2023)

Effects of Aeromonas hydrophila infection on the intestinal microbiota, transcriptome, and metabolomic of common carp (Cyprinus carpio) - Lan Zhang; Lei Wang; Jintai Huang; Zhan Jin; Junxiang Guan; Hang Yu; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao (Fish & Shellfish Immunology, 2023)

Comparative study on nutritional quality and serum biochemical indices of common carp (Cyprinus carpio) aged 11 to 13 months aged cultured in traditional ponds and land-based container aquaculture systems - Fangran Ma; Lei Wang; Jintai Huang; Yuhan Chen; Lan Zhang; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao (Food Research International, 2023)

Genipin-mediated subunit-subunit crosslinking of ferritin nanocages: Structure, properties, and its application for food bioactive compound sealing - Hai Chen; Xiaoyi Tan; Mengji Hu; Jiang Xie; Xueer Han; Yong Yu; Hankun Zhu; Hongxia Wang; Yuhao Zhang (Food Chemistry, 2023)

Triple-induced gardenia fruit extract-enriched gelatin/polysaccharides microgels for O/W emulsions, and food 3D printing - Zhiying Ouyang; Juncheng Zhu; Yang Cheng; Liangzhe Chen; Yuxin Yang; Liang Ma; Hankun Zhu; Yong Yu; Yuhao Zhang; Hongxia Wang (Food Bioscience, 2023)

Myofibrillar protein microgels stabilized high internal phase Pickering emulsions with heat-promoted stability - Hongjie Dai; Yi Sun; Xin Feng; Liang Ma; Hai Chen; Yu Fu; Hongxia Wang; Yuhao Zhang (Food Hydrocolloids, 2023)

Structure maintainability of safflomin/betanin incorporated gelatin-chitooligosaccharide complexes based high internal phase emulsions and its combinational 3D printing - Hongxia Wang; Zhiying Ouyang; Yang Cheng; Juncheng Zhu; Yuxin Yang; Liang Ma; Hongjie Dai; Hai Chen; Jia Yu; Shihao Qiao; Yuhao Zhang (Food Hydrocolloids, 2023)

Prediction of zebrafish embryonic developmental toxicity by integrating omics with adverse outcome pathway - Xiao Gou; Cong Ma; Huimin Ji; Lu Yan; Pingping Wang; Zhihao Wang; Yishan Lin; Nivedita Chatterjee; Hongxia Yu; Xiaowei Zhang (Journal of Hazardous Materials, 2023)

Recent advances in protein-based emulsions: The key role of cellulose - Hongjie Dai; Yuyuan Luo; Yue Huang; Liang Ma; Hai Chen; Yu Fu; Yong Yu; Hankun Zhu; Hongxia Wang; Yuhao Zhang (Food Hydrocolloids, 2023)

Houttuynia cordata Thunb. crude extract inactivates Cronobacter sakazakii: Antibacterial components, antibacterial mechanism, and application as a natural disinfectant - Yunhe Chang; Shiwen Xia; Peng Fei; Hongxia Feng; Fangyu Fan; Yu Liu; Likang Qin; Lizhi Ma; Qianhua Song; Yonghong Liu (Food Control, 2023)

Human functional genomics reveals toxicological mechanism underlying genotoxicants-induced inflammatory responses under low doses exposure - Mingming Tian; Pu Xia; Lu Yan; Xiao Gou; Hongxia Yu; Xiaowei Zhang (Chemosphere, 2023)

Volatile potassium transfer behavior in carbon matrix and its effect on char gasification - Xingjun Wang; Qian Chen; Bing Wei; Guangsuo Yu; Hongxia Li; Xueli Chen; Haifeng Liu; Fuchen Wang (Fuel, 2023)

Gelatin films functionalized by lignocellulose nanocrystals-tannic acid stabilized Pickering emulsions: Influence of cinnamon essential oil - Hongjie Dai; Yuan Chen; Hai Chen; Yu Fu; Liang Ma; Hongxia Wang; Yong Yu; Hankun Zhu; Yuhao Zhang (Food Chemistry, 2023)

QTL Mapping of Growth Traits in Yellow River Carp (Cyprinus carpio haematopterus) at 5–17 Months after Hatching - Yuhan Chen; Jintai Huang; Zhan Jin; Junping Chen; Meng Zhang; Miao Yu; Hongxia Jiang; Lei Wang; Zhigang Qiao (Fishes, 2023)
To screen the quantitative trait loci (QTL) and genes related to the growth of Yellow River carp (Cyprinus carpio haematopterus) after removing the maternal effect, we established a family of these carps. Four growth-related traits (body length, height, thickness, and weight) of the family at 5 and 17 months after hatching (MAH) were measured. Analysis of QTL mapping for the four growth-related traits was conducted using the genetic linkage map constructed in our laboratory. We identified 47 QTL that were related to the four growth traits and three consensus QTL (cQTL). A total of 10, 14, 10, and 13 QTL were associated with body length, height, thickness, and weight, respectively; cQTL-1, cQTL-2, and cQTL-3 contained 11, 2, and 2 QTL, respectively. We detected 17 growth-related candidate genes within 50 Kb upstream and downstream of the five main-effect QTL (phenotypic variation explained > 10%, logarithm of odds > 5.5). Two genes (cbfa2t2 and neca1) that may be affected by maternal effects were identified by comparing the main-effect QTL at 17 and 5–17 MAH. This study was the first attempt to eliminate growth-related QTL and genes affected by maternal effects in Yellow River carp. These results can be used in molecular marker-assisted breeding and provide valuable genomic resources for the genetic mechanisms underlying growth in Yellow River carp.

Impact of biochar colloids on thallium(I) transport in water-saturated porous media: Effects of pH and ionic strength - Yu Cao; Chengxue Ma; Jinni Yao; Wanpeng Chen; Li Gu; Hongxia Liu; Caihong Liu; Jiaming Xiong; Xiaoliu Huangfu (Chemosphere, 2023)

Identification of high-concern organic pollutants in tap waters from the Yangtze River in China based on combined screening strategies - Liben Chou; Chengzhuo Zhou; Wenrui Luo; Jing Guo; Yanhong Shen; Die Lin; Chang Wang; Hongxia Yu; Xiaowei Zhang; Si Wei; Wei Shi (Science of The Total Environment, 2023)

Numerical Simulation Study of Double-Emulsion Droplet Formation in a Co-flow Microchannel Capillary Device - Qing Yu; Yongbiao Ma; Xiaoyu Li; Hongxia Zheng; Xueye Chen (Transport in Porous Media, 2022)

Preparation of β-cyclodextrin/dopamine hydrochloride-graphene oxide and its adsorption properties for sulfonamide antibiotics - Hongxia Yu; Kun Zheng; Xiaoying Xu; Xiaowei Liu; Bin Zhao; Haitao Ding; Zhimin Yu; Chengxun Deng (Environmental Science and Pollution Research, 2022)

Co/N co-doped porous carbon as a catalyst for the degradation of RhB by efficient activation of peroxymonosulfate - Hongxia Yu; Dan Ding; Shuailing Zhao; Muhammad Faheem; Weijie Mao; Li Yang; Liwei Chen; Tianming Cai (Environmental Science and Pollution Research, 2022)

Mapping Growth-Related Quantitative Trait Locus (QTL) in Commercial Yellow River Carp (Cyprinus carpio haematopterus) during Overwintering - Lei Wang; Lan Zhang; Yuhan Chen; Junping Chen; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Xuejun Li (Fishes, 2022)
The common carp (Cyprinus carpio) is farmed globally; as a subspecies, the Yellow River carp (C. c. haematopterus) is widely farmed in northern China. Since the Yellow River carp grows slowly in winter, it would benefit breeders to implement a breeding program targeting growth in winter. In May 2017, we established a Yellow River carp family and measured the body length, height, thickness, and weight of individuals before (October 2017) and after winter (February 2018). Based on the genetic linkage map established in our laboratory, the quantitative trait locus (QTL) mapping of these four traits led to the detection of 29 growth-related QTLs, of which 9, 7, 3, and 10 QTLs were associated with body length, height, thickness, and body weight, respectively. One consensus QTL contained seven QTLs associated with four traits. Through the two major-effect QTLs (qBL-p-1 and qBL-p-2), we screened three candidate genes (fnd3b, ghsr, and pld1), which were associated with biological activities, such as fat formation, growth, and membrane transport. These results are helpful in exploring the growth regulation mechanism and providing a reference for genetic breeding with regard to the overwintering growth of Yellow River carp.

Neuroimaging-ITM: A Text Mining Pipeline Combining Deep Adversarial Learning with Interaction Based Topic Modeling for Enabling the FAIR Neuroimaging Study - Jianzhuo Yan; Lihong Chen; Yongchuan Yu; Hongxia Xu; Zhe Xu; Ying Sheng; Jianhui Chen (Neuroinformatics, 2022)

CD146 as a promising therapeutic target for retinal and choroidal neovascularization diseases - Bai Xue; Ping Wang; Wenzhen Yu; Jing Feng; Jie Li; Rulian Zhao; Zhenglin Yang; Xiyun Yan; Hongxia Duan (Science China Life Sciences, 2022)

Menin regulates lipid deposition in mouse hepatocytes via interacting with transcription factor FoxO1 - Shengxuan Wang; Tingjun Liu; Lili Sun; Hongxia Du; Zhongjin Xu; Ranran Li; Ying Yu; Yongjiang Mao; Kerong Shi (Molecular and Cellular Biochemistry, 2022)

The neonatal PROC gene rs1799809 polymorphism modifies the association between prenatal air pollutants exposure and PROC promoter methylation - Zhiyuan Li; Meng Yang; Leizhen Duan; Yongxiang Gong; Hongxia Xia; Francis-Kojo Afrim; Hui Huang; Xiaoxue Liu; Fangfang Yu; Yawei Zhang; Yue Ba; Guoyu Zhou (Environmental Science and Pollution Research, 2022)

The Flavor and Antioxidant Activity Change Pattern of Shrimp Head Paste During Fermentation - Jing Yu; Kuan Lu; Jinyuan Sun; Wancui Xie; Lin Song; Hongxia Che (Journal of Ocean University of China, 2022)

Long non-coding RNA TTC28-AS1 attenuates high glucose-induced damage in HK-2 cells depending on the regulation of miR-320a/CD2AP axis - Ji Zhang; Juan Ding; Ming Yu; Fang Li; Xue Zhou; Hongxia Shuai (Genes & Genomics, 2021)

GmFULa improves soybean yield by enhancing carbon assimilation without altering flowering time or maturity - Yanlei Yue; Shi Sun; Jiawen Li; Haidong Yu; Hongxia Wu; Baiquan Sun; Tao Li; Tianfu Han; Bingjun Jiang (Plant Cell Reports, 2021)
Key message GmFULa improved soybean yield by enhancing carbon assimilation. Meanwhile, different from known yield-related genes, it did not alter flowering time or maturity. Abstract Soybean ( Glycine max (L.) Merr.) is highly demanded by a continuously growing human population. However, increasing soybean yield is a major challenge. FRUITFULL ( FUL ), a MADS-box transcription factor, plays important roles in multiple developmental processes, especially fruit and pod development, which are crucial for soybean yield formation. However, the functions of its homologs in soybean are not clear. Here, through haplotype analysis, we found that one haplotype of the soybean homolog GmFULa ( GmFULa-H02 ) is dominant in cultivated soybeans, suggesting that GmFULa-H02 was highly selected during domestication and varietal improvement of soybean. Interestingly, transgenic overexpression of GmFULa enhanced vegetative growth with more biomass accumulated and ultimately increased the yield but without affecting the plant height or changing the flowering time and maturity, indicating that it enhances the efficiency of dry matter accumulation. It also promoted the yield factors like branch number, pod number and 100-seed weight, which ultimately increased the yield. It increased the palisade tissue cell number and the chlorophyll content to promote photosynthesis and increase the soluble sugar content in leaves and fresh seeds. Furthermore, GmFULa were found to be sublocalized in the nucleus and positively regulate sucrose synthases ( SUSs ) and sucrose transporters ( SUTs ) by binding with the conserved CArG boxes in their promoters. Overall, these results showed GmFULa promotes the capacity of assimilation and the transport of the resultant assimilates to increase yield, and provided insights into the link between GmFULa and sucrose synthesis with transport-related molecular pathways that control seed yield.

Comparison of the Digestion and Absorption Characteristics of Docosahexaenoic Acid-Acylated Astaxanthin Monoester and Diester in Mice - Ye Li; Jie Yu; Jie Xu; Hongxia Che; Yuming Wang; Changhu Xue; Qingrong Huang; Tiantian Zhang (Journal of Ocean University of China, 2021)

Co-substrate facilitated charge transfer for bioelectricity evolution in a toxic blue-green alga-fed microbial fuel cell technology - Fabrice Ndayisenga; Zhisheng Yu; Telesphore Kabera; Bobo Wang; Hongxia Liang; Irfan Ali Phulpoto; Telesphore Habiyakare; Yvan Kalisa Ndayambaje; Xinyu Yan (Clean Technologies and Environmental Policy, 2021)

Identification, expression and enzyme activity of the group III sPLA 2 s in Cyprinus carpio L - Yuxin Xu; Hongxia Li; Dihui Xu; Jianlin Li; Fan Yu; Meiyao Wang; Qin Wang; Yunsheng Wu; Qiyuan Zhang; Yongkai Tang; Juhua Yu (Journal of Fish Biology, 2021)
Five group III secreted phospholipase (pla2g3s) homologous genes located on different linkage groups were identified from common carp ( Cyprinus carpio ), which we named Ccpla2g3a1 , Ccpla2g3a2 , Ccpla2g3b , Ccpla2g3c1 and Ccpla2g3c2 . The five genes encode 530, 525, 461, 752 and 753 amino acids, respectively. Sequence analysis showed that the Ccpla2g3a s contain seven exons and the others contain four exons. Synteny analysis of fish pla2g3s indicated that pla2g3a and pla2g3b were from the same ancestor gene, and Ccpla2g3a 1, Ccpla2g3a 2, Ccpla2g3c 1 and Ccpla2g3c 2 were from the specific genome duplication of common carp. Due to the significant variation of the pla2g3bs from common carp and zebrafish ( Danio rerio ), they formed a separate group in the phylogenetic tree. The tissue distributions of Ccpla2g3 s coincided with their expression profiles during the embryo stages. The expression levels of Ccpla2g3a s and Ccpla2g3c s were low at the embryo stages, and they were abundant in the liver and brain, respectively, whereas the expression of Ccpla2g3b was high at 0.5 h after fertilization and in the ovary. We obtained three soluble recombinant proteins of the bee venom‐like PLA2 (BVLP) from Ccpla2g3 and evaluated their PLA 2 enzyme properties. The optimum pHs of MBP‐a1‐BVLP, MBP‐b‐BVLP and MBP‐c1‐BVLP were 7.5, 7.0 and 8.0, respectively, and specific activities were 7.68 ± 0.66, 4.155 ± 0.158 and 1.93 ± 0.05 U μmol –1 , respectively. The K d for Ca 2+ of MBP‐b‐BVLP was the lowest (2.6 μM), whereas the values for both MBP‐a1‐BVLP and MBP‐c1‐BVLP were about 15 μM. The K m values of three proteins ranged from 31.9 to 41.91 μM.

Characterization and complete genome analysis of Bacillus velezensis CB6 revealed ATP synthase subunit α against foodborne pathogens - Haipeng Zhang; Guan-yi Xu; Changsi Mao; Yuxuan Xu; Wenlong Dong; Muhammad Inam; Siyu Pan; Renge Hu; Yiming Wang; Yu Wang; Hongxia Ma; Lingcong Kong (Archives of Microbiology, 2021)

NEAT1 Decreasing Suppresses Parkinson’s Disease Progression via Acting as miR-1301-3p Sponge - Qiang Sun; Yueliang Zhang; Songlin Wang; Fang Yang; Hongxia Cai; Yu Xing; Zengfeng Chen; Jun Chen (Journal of Molecular Neuroscience, 2021)

Risks Assessment Associated with Different Sources of Metals in Abandoned Soil of Zhuxianzhuang Coal Mine, Huaibei Coalfield (Anhui, China) - Hongxia Fang; Herong Gui; Jun Li; Hao Yu; Meichen Wang; Yaqi Jiang; Chunlei Wang; Chen Chen; Yaru Zhang; Yiheng Huang (Bulletin of Environmental Contamination and Toxicology, 2021)

Microbial community changes in the digestive tract of the clam Meretrix petechialis in response to Vibrio parahaemolyticus challenge - Hongxia Wang; Xin Yue; Jiajia Yu; Rui Wang; Shuangshuang Teng; Jun Fang; Baozhong Liu (Journal of Oceanology and Limnology, 2021)

Identification and characterization of the strawberry KT/HAK/KUP transporter gene family in response to K+ deficiency - Yachao Gao; Chunyan Yu; Kai Zhang; Hongxia Zhang; Shaoying Zhang; Zhizhong Song (Acta Physiologiae Plantarum, 2021)

The application of exogenous PopW increases the tolerance of Solanum lycopersicum L. to drought stress through multiple mechanisms - Xiaosi Zhou; Yu Chen; Yangyang Zhao; Fangyuan Gao; Hongxia Liu (Physiology and Molecular Biology of Plants, 2020)

Sex Difference Between Trace Elements and Pulmonary Functions in Children - Zhenzhen Pan; Xiaojuan Zhang; Yu Hui; Hongxia Xiang; Qian Wang; Shiyao Xu; Ling Li (Biological Trace Element Research, 2020)

Allelochemical-driven N preference switch from NO3− to NH4+ affecting plant growth of Cunninghamia lanceolata (lamb.) hook - Lulu Yu; Hongxia Zhao; Guangdeng Chen; Shu Yuan; Ting Lan; Jian Zeng (Plant and Soil, 2020)

Calcium Ions Turn on the Fluorescence of Oxytetracycline for Sensitive and Selective Detection - Hongxia Chen; Junxiang Peng; Long Yu; Hui Chen; Mingtai Sun; Zhenli Sun; Runyan Ni; Khalid A. Alamry; Hadi M. Marwani; Suhua Wang (Journal of Fluorescence, 2020)

Heritability of resistance-related gene expression traits and their correlation with body size of clam Meretrix petechialis - Fengjuan Jiang; Xin Yue; Shujing Zhang; Jiajia Yu; Rui Wang; Baozhong Liu; Hongxia Wang (Journal of Oceanology and Limnology, 2020)

Effects of Lead, Mercury, and Cadmium Co-exposure on Children’s Pulmonary Function - Zhenzhen Pan; Yun Guo; Hongxia Xiang; Yu Hui; Huili Ju; Shiyao Xu; Ling Li (Biological Trace Element Research, 2020)

Urban VOC profiles, possible sources, and its role in ozone formation for a summer campaign over Xi’an, China - Jian Sun; Zhenxing Shen; Yue Zhang; Zhou Zhang; Qian Zhang; Tian Zhang; Xinyi Niu; Yu Huang; Long Cui; Hongmei Xu; Hongxia Liu; Junji Cao; et al. (Environmental Science and Pollution Research, 2019)

Geodynamic transition from subduction to extension: evidence from the geochronology and geochemistry of granitoids in the Sangsang area, southern Lhasa Terrane, Tibet - Feng Huang; Mingjian Li; Jifeng Xu; Yunchuan Zeng; Jianlin Chen; Baodi Wang; Hongxia Yu; Ling Chen; Peipei Zhao; Zhao Zhang (International Journal of Earth Sciences, 2019)

Reinforcement of resistance of modern rose to black spot disease via hybridization with Rosa rugosa - Tingliang Xu; Yuying Wu; Xingwan Yi; Jiongrui Tan; Hongxia Zhao; Chao Yu; Le Luo; Tangren Cheng; Jia Wang; Huitang Pan; Qixiang Zhang (Euphytica, 2018)

Characteristics and phylogenetic analysis of the complete mitochondrial genome of Lagocephalus inermis (Tetraodontiformes; Tetraodontidae) - Yu Wang; Lingcong Kong; Hongxia Ma; Yunhang Gao (Conservation Genetics Resources, 2018)

Physiological and transcriptomic analyses of a yellow-green mutant with high photosynthetic efficiency in wheat (Triticum aestivum L.) - Yu Wang; Wei Zheng; Weijun Zheng; Jianchu Zhu; Zhenshan Liu; Jinxia Qin; Hongxia Li (Functional & Integrative Genomics, 2018)

Prior contact of Pinus tabulaeformis with ectomycorrhizal fungi increases plant growth and survival from damping-off - Haoqiang Zhang; Hongxia Yu; Ming Tang (New Forests, 2017)

A cis-eQTL genetic variant of the cancer–testis gene CCDC116 is associated with risk of multiple cancers - Na Qin; Cheng Wang; Qun Lu; Tongtong Huang; Meng Zhu; Lihua Wang; Fei Yu; Mingtao Huang; Yue Jiang; Juncheng Dai; Hongxia Ma; Guangfu Jin; et al. (Human Genetics, 2017)

A New Non-Darcy Flow Model for Low-Velocity Multiphase Flow in Tight Reservoirs - Yi Xiong; Jinbiao Yu; Hongxia Sun; Jiangru Yuan; Zhaoqin Huang; Yu-shu Wu (Transport in Porous Media, 2017)

Effects of 3,5-Diiodotyrosine and Potassium Iodide on Thyroid Function and Oxidative Stress in Iodine-Excess Wistar Rats - Dan Liu; Xinying Lin; Fugui Yu; Man Zhang; Hongxia Chen; Wei Bao; Xia Wang (Biological Trace Element Research, 2015)

Industrial spatial agglomeration using distance-based approach in Beijing, China - Jiaming Li; Wenzhong Zhang; Jianhui Yu; Hongxia Chen (Chinese Geographical Science, 2015)

Comparison on the molecular response profiles between nano zinc oxide (ZnO) particles and free zinc ion using a genome-wide toxicogenomics approach - Guanyong Su; Xiaowei Zhang; John P. Giesy; Javed Musarrat; Quaiser Saquib; Abdulaziz A. Alkhedhairy; Hongxia Yu (Environmental Science and Pollution Research, 2015)

Identification of polycyclic aromatic hydrocarbons in soils in Taizhou, East China - Guanjiu Hu; Sulan Chen; Wei Shi; Beibei Zhang; Yong Zhang; Juan Huang; Jun Chen; John P. Giesy; Hongxia Yu (Environmental Geochemistry and Health, 2015)

Prey-mediated effects of transgenic cry2Aa rice on the spider Hylyphantes graminicola, a generalist predator of Nilapavarta lugens - Yu Han; Jie Chen; Hui Wang; Jing Zhao; Yueping He; Hongxia Hua (BioControl, 2015)

Comparison of waterborne and in ovo nanoinjection exposures to assess effects of PFOS on zebrafish embryos - Yabing Li; Zhihua Han; Xinmei Zheng; Zhiyuan Ma; Hongling Liu; John P. Giesy; Yuwei Xie; Hongxia Yu (Environmental Science and Pollution Research, 2015)

Characterization and expression analysis of two distinct neuropeptide Ya paralogues in Jian carp (Cyprinus carpio var. Jian) - Yongkai Tang; Hongxia Li; Jianlin Li; Fan Yu; Juhua Yu (Fish Physiology and Biochemistry, 2014)

Weighted species sensitivity distribution method to derive site-specific quality criteria for copper in Tai Lake, China - Rui Shi; Chunhui Yang; Runhua Su; Jiarui Jin; Yi Chen; Hongling Liu; John P. Giesy; Hongxia Yu (Environmental Science and Pollution Research, 2014)

Monitoring of non-destructive sampling strategies to assess the exposure of avian species in Jiangsu Province, China to heavy metals - Jie Fu; Qing Wang; Hui Wang; Hongxia Yu; Xiaowei Zhang (Environmental Science and Pollution Research, 2014)

Dioxin-like activity in sediments from Tai Lake, China determined by use of the H4IIE-luc bioassay and quantification of individual AhR agonists - Jie Xia; Guanyong Su; Xiaowei Zhang; Wei Shi; John P. Giesy; Hongxia Yu (Environmental Science and Pollution Research, 2014)

Effects of multigenerational exposures of D. magna to environmentally relevant concentrations of pentachlorophenol - Yi Chen; Jin Huang; Liqun Xing; Hongling Liu; John P. Giesy; Hongxia Yu; Xiaowei Zhang (Environmental Science and Pollution Research, 2014)

A comparison of statistical methods for deriving freshwater quality criteria for the protection of aquatic organisms - Liqun Xing; Hongling Liu; Xiaowei Zhang; Markus Hecker; John P. Giesy; Hongxia Yu (Environmental Science and Pollution Research, 2014)

Expression kinetics of chicken β2-microglobulin and Class I MHC in vitro and in vivo during Marek’s disease viral infections - Chuan Yu; Qiu Liu; Aijian Qin; Xuming Hu; Wencai Xu; Kun Qian; Hongxia Shao; Wenjie Jin (Veterinary Research Communications, 2013)

Molecular Modeling and Molecular Dynamics Simulation Studies on the Interactions of Hydroxylated Polychlorinated Biphenyls with Estrogen Receptor-β - Xiaolin Li; Li Ye; Xiaoxiang Wang; Wei Shi; XiangPing Qian; YongLiang Zhu; HongXia Yu (Archives of Environmental Contamination and Toxicology, 2013)

Transcriptional profile of Marek’s disease virus genes in chicken thymus during different phases of MDV infection - Xuming Hu; Aijian Qin; Ji Miao; Wencai Xu; Chuan Yu; Kun Qian; Hongxia Shao (Archives of Virology, 2013)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

Mechanisms of toxicity of triphenyltin chloride (TPTC) determined by a live cell reporter array - Guanyong Su; Xiaowei Zhang; Jason C. Raine; Liqun Xing; Eric Higley; Markus Hecker; John P. Giesy; Hongxia Yu (Environmental Science and Pollution Research, 2013)

Quantitative Structure–Activity Relationship for Prediction of the Toxicity of Phenols on Photobacterium phosphoreum - Xiaolin Li; Zunyao Wang; Hongling Liu; Hongxia Yu (Bulletin of Environmental Contamination and Toxicology, 2012)

Field evaluation of effects of transgenic cry1Ab/cry1Ac, cry1C and cry2A rice on Cnaphalocrocis medinalis and its arthropod predators - XueLiang Xu; Yu Han; Gang Wu; WanLun Cai; BenQi Yuan; Hui Wang; FangZhou Liu; ManQun Wang; HongXia Hua (Science China Life Sciences, 2011)

Identification of trace organic pollutants in freshwater sources in Eastern China and estimation of their associated human health risks - Wei Shi; Fengxian Zhang; Xiaowei Zhang; Guanyong Su; Si Wei; Hongling Liu; Shupei Cheng; Hongxia Yu (Ecotoxicology, 2011)

Lead-contaminated soil induced oxidative stress, defense response and its indicative biomarkers in roots of Vicia faba seedlings - Chengrun Wang; Yuan Tian; Xiaorong Wang; Jinju Geng; Jinlin Jiang; Hongxia Yu; Chen Wang (Ecotoxicology, 2010)

Endocrine-disrupting equivalents in industrial effluents discharged into Yangtze River - Wei Shi; Xiaoyi Wang; Wei Hu; Hong Sun; Ouxi Shen; Hongling Liu; Xinru Wang; John P. Giesy; Shupei Cheng; Hongxia Yu (Ecotoxicology, 2009)

Microsatellite-centromere distances and microsatellite diversity in different ploidy classes of Chinese shrimp (Fenneropenaeus Chinensis) - Hongxia Wang; Fuhua Li; Jianhai Xiang; Chengsong Zhang; Kuijie Yu (Genetica, 2007)